THE MAIN CHARACTERISTICS OF LUBRICATION FOR WIRE DRAWING FOR METAL CORD, THEIR INFLUENCE ON DRAWING QUALITY - A. A. Truhanovich; A. A. Ledneva (Литьë и металлургия, 2008)
The physical-chemical characteristics of lubrications for dry wiredrawing are examined. The connection of some parameters with quality of both the drawing process and finished wire is shown.